PERBAIKAN JATUH TEGANGAN PADA FEEDER B KB 31P SETIABUDI JAKARTA DENGAN METODE PECAH BEBAN - Ishak Kasim; Chairul Gagarin Irianto; Fachrizal Fachrizal (Website, 2013)
Abstract The need for electricity in Indonesia now increases , along with an increase in the number of customers , which is industry and households. With the increasing need for electricity at the moment, the level of reliability of the electrical system becomes very important thing to guarantee the continuity for supply of power to consumers. In this final assignment will be discussed regarding repairs voltage drop at the feeder B KB 31P in Setia Budi Jakarta method breaks the load. Falling voltage on the network is very closely associated with the increasing load on each phase. The magnitude of the voltage and the voltage drop size on feeder network tip B KB 31P will be analysis of data by using two measurements which are in the daytime and night-time before and after a splits load will then be compared to the standard service voltage variations that have been determined by PLN. Keywords: network, intrusion, detection, snort, flooding.